Use of the Kessler Psychological Distress Scale in the HILDA Survey - Wooden, M (My University, 2009)
This short paper briefly describes the K10 and the measures derived from it and included in the HILDA Survey data release 7.0, makes some brief comparisons with the mental health sub-scale of the SF36, and reports how population estimates from the HILDA Survey compare with those from ABS sources (namely, the NHS and the NSMHWB).
HILDA PROJECT DISCUSSION PAPER SERIES No. 2/09, February 2009
Keywords: Health -- Mental; Surveys and Survey Methodology -- Questionnaire development; Surveys and Survey Methodology; Health and wellbeing; Surveys and survey methodology; Surveys and Survey Methodology; Health; Mental; Questionnaire development; Health and wellbeing; Surveys and Survey Methodology